2018
DOI: 10.1080/14767058.2018.1506438
|View full text |Cite
|
Sign up to set email alerts
|

Measuring fetal adipose tissue using 3D water-fat magnetic resonance imaging: a feasibility study

Abstract: 3D water-fat MRI can reliably measure volume and quantify lipid content of fetal subcutaneous adipose tissues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…The fat signal fraction of fetal AT has been found to increase with GA but was still lower than the fat fractions of both neonatal and mature adult AT of 77.9% and 90%, respectively. 6,37 Hence, AT development continuing beyond the investigated period could explain the decrease in both water and lipid T 1 with gestation. Furthermore, the water and lipid T 1 values did not significantly vary between compartments, indicating that water and lipid T 1 of AT as a function of GA does not depend on AT location, respectively.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The fat signal fraction of fetal AT has been found to increase with GA but was still lower than the fat fractions of both neonatal and mature adult AT of 77.9% and 90%, respectively. 6,37 Hence, AT development continuing beyond the investigated period could explain the decrease in both water and lipid T 1 with gestation. Furthermore, the water and lipid T 1 values did not significantly vary between compartments, indicating that water and lipid T 1 of AT as a function of GA does not depend on AT location, respectively.…”
Section: Discussionmentioning
confidence: 96%
“…16 It is important to quantify these relaxation times over GA because fetal tissues develop structurally throughout gestation; for instance, the fat fraction of adipose tissue (AT) is known to increase with GA in the third trimester. 6 Since both T 1 and T 2 * are sensitive to tissue microstructure, AT and other fetal organ structural changes may likely cause changes in T 1 and T 2 * throughout gestation. 17 The quantification of fetal tissue relaxation times as a function of GA will provide insight into fetal tissue development, facilitate comparison of images acquired at different GA, and contribute to methodologies with clinical utility.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has not been used for investigation of fetal adipose until the recent development of MRI acquisitions fast enough to freeze fetal motion. 174 These first studies showed that fetal WAT is significantly different than WAT in children or adults, with substantially lower lipid contentthat content is increasing rapidly during the third trimester. These and other differences between fetal BAT and mature WAT complicate the differentiation of WAT and BAT in utero, since MRI methods that can successfully differentiate mature WAT and BAT rely on assumptions that are not valid in fetal life, 175 or use techniques that are poorly suited to fetal imaging such as BOLD, 176 xenon MRI, 177 and zero-quantum coherence.…”
Section: Application Of Mri To Differentiate Between Brown and White mentioning
confidence: 99%
“…These and other differences between fetal BAT and mature WAT complicate the differentiation of WAT and BAT in utero, since MRI methods that can successfully differentiate mature WAT and BAT rely on assumptions that are not valid in fetal life, 175 or use techniques that are poorly suited to fetal imaging such as BOLD, 176 xenon MRI, 177 and zero-quantum coherence. 178 Techniques that show promise for fetal WAT/BAT differentiation include quantification of proton-density fat fraction (PDFF), 174,179,180 quantification of fatty acid composition (FAC), 181 and adipose tissue relaxometry, particularly T2*; however, all of these methods need further development before they can be considered valid tools for BAT detection. PDFF quantification can differentiate WAT and BAT, but only after 30 weeks of gestational age when the PDFF of WAT and BAT are sufficiently different.…”
Section: Application Of Mri To Differentiate Between Brown and White mentioning
confidence: 99%